Study of Traumatic Brain Injury Due To Recent Earthquake in Manipal Teaching Hospital - Karmacharya, Bal G; Sathian, Brijesh (Nepal Journal of Neuroscience, 2016)
The objective of this study was to review the demographics, causes injury, severity, treatment and outcome of traumatic brain injuries in victims of the April 2015 earthquake who were admitted in Manipal Teaching Hospital, Pokhara. A total of 37 patients was admitted under Neurosurgery Services. Collapse of buildings was the commonest cause of head injury. The majority of them had mild head injury. Associated injuries to other parts of the body were present in 40.54% patients. Nepal Journal of Neuroscience 12:63-66, 2015